Serum calprotectin in nonsegmental vitiligo: a possible marker of disease activity - Dalia A. Bassiouny; Yasmin B. El Zawahry; Ahmed M. Soliman; Alaa H. Sayed; Eman R. Youness; Dina G. Saadi (Journal of the Egyptian Women’s Dermatologic Society)
Background Determining the status of nonsegmental vitiligo is crucial in initiating the management plan, especially when planning for surgery. Serum biomarkers can serve as an additive tool, to clinical examination and history-taking, in differentiating active from stable vitiligo. Objective To assess serum levels of calprotectin (CP) in nonsegmental vitiligo, and to compare these levels among active and stable cases. Patients and methods Serum samples were taken from 42 vitiligo patients and 42 healthy controls, and CP levels were measured by ELISA technique. Results Although the serum CP levels were not significantly higher in patients (median = 33.6) in comparison with controls (median = 33.5) (P=0.28), CP was significantly elevated in active vitiligo cases when compared with stable patients (P=0.010) and had a positive correlation with vitiligo disease activity score (r=0.400, P=0.009). Conclusion Serum CP can potentially help in differentiating active from stable vitiligo.